Case report: Primary cardiac undifferentiated sarcoma complicated by esophagus stenosis - Ge, Yuxin; Lv, Xiaopan; Zhang, Rui; Hao, Dongxiao; Si, Guifei; Li, Yuquan; Yuan, Xuemin; Li, Xiuping (Frontiers in Oncology, 2025)
In this study, we present the case of a 38-year-old woman who was diagnosed with primary cardiac undifferentiated sarcoma after hospital admission. Following postoperative treatment that included radiotherapy and immunotherapy, the patient developed esophagus stenosis.